2013
DOI: 10.1016/j.tetlet.2013.09.100
|View full text |Cite
|
Sign up to set email alerts
|

An improved synthesis and some reactions of diethyl 4-oxo-4H-pyran-2,5-dicarboxylate

Abstract: Ethyl 2-(dimethylamino)methylene-3-oxobutanoate Diethyl oxalate 4-Oxo-4H-pyran-2,5-dicarboxylic acid 4-Oxo-1-phenyl-1,4-dihydropyridine-2,5-dicarboxylic acid a b s t r a c tThe reaction of ethyl 2-(dimethylamino)methylene-3-oxobutanoate with diethyl oxalate in the presence of sodium hydride in THF gave diethyl 4-oxo-4H-pyran-2,5-dicarboxylate, from which 4-oxo-4H-pyran-2,5-dicarboxylic and 4-oxo-1-phenyl-1,4-dihydropyridine-2,5-dicarboxylic acids and their derivatives were obtained in good yields.Ó 2013 Elsevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
7
0
3
Order By: Relevance
“…The yields of all of the stages were low to moderate during the initial optimization either due to lower conversion or due to formation of more impurities. The first stage, namely, ring opening of 2 with aminoacetaldehyde dimethyl acetal, proceeded instantaneously to form a mixture of acyclic intermediates, which cyclized to 3 in varying yields and purity depending upon the conditions employed. A preliminary screening of solvents (ester, chlorinated, hydrocarbon, and protic solvents) pointed out that the reaction was efficient in alcoholic solvent, especially methanol (Table S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The yields of all of the stages were low to moderate during the initial optimization either due to lower conversion or due to formation of more impurities. The first stage, namely, ring opening of 2 with aminoacetaldehyde dimethyl acetal, proceeded instantaneously to form a mixture of acyclic intermediates, which cyclized to 3 in varying yields and purity depending upon the conditions employed. A preliminary screening of solvents (ester, chlorinated, hydrocarbon, and protic solvents) pointed out that the reaction was efficient in alcoholic solvent, especially methanol (Table S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…All solvents used were dried and distilled by standard procedures. Known pyrones 1 were prepared by literature procedures …”
Section: Methodsmentioning
confidence: 99%
“…To increase chemical reactivity of the pyrone ring, we decided to introduce additional electron-withdrawing group at the C-5 position. We have chosen to use readily available derivatives of 5-acyl-4-pyrone-2-carboxylic acid because these compounds contain the oxymethylidenediketone core, which exhibits high reactivity with indoles . Also, in previous research, these pyrones were reported to react smoothly with water as well as with primary and secondary amines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Особый интерес в области разработки остеогенных средств привлекают так называемые «малые» молекулы с остеогенными свойствами, к которым относится и хелидоновая кислота (ХК), содержащаяся в ряде лекарственных растений, которая обладает различными видами биологической активности, в том числе, и остеогенной [6][7][8][9].…”
Section: Introductionunclassified